Evaluation of early hospital discharge after allogeneic bone marrow transplantation for chronic myeloid leukemia - Nicolau, José Eduardo; Melo, Leila Maria Magalhães Pessoa de; Sturaro, Daniel; Saboya, Rosaura; Dulley, Frederico Luiz (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: The increasing number of patients waiting for bone marrow transplantation in our service led to the implement of an early hospital discharge program with the intention of reducing the interval between diagnosis and transplantation. In this study we analyzed the results from early discharge, with outpatient care for patients with chronic myeloid leukemia who underwent allogeneic bone marrow transplantation. DESIGN AND SETTING: Retrospective study at the Bone Marrow Transplantation Unit of Hospital das Clínicas, Faculdade de Medicina da Universidade de São Paulo. METHODS: We compared clinical outcomes within 100 days post-transplantation, for 51 patients with chronic myeloid leukemia (CML) who received partially outpatient-based allogeneic hematopoietic stem cell transplantation, and the results were compared with a historical control group of 49 patients who received inpatientbased hematopoietic stem cell transplantation. RESULTS: There were significantly fewer days of hospitalization (p = 0.004), Pseudomonas-positive cultures (p = 0.006) and nausea and vomiting of grade 2-3 (p < 0.001) in the outpatient group. There were no significant differences in mortality between the groups and no deaths occurred within the first 48 days post-transplantation in the outpatient group. CONCLUSIONS: This partially outpatient-based hematopoietic stem cell transplantation program allowed an increased number of transplantations in our institution, in cases of CML and other diseases, since it reduced the median length of hospital stay without increasing morbidity and mortality.